An overview of stock management in aministration unit Department of Islamic Judiciary / Nuramal Alia Ahmad Halimi - Ahmad Halimi, Nuramal Alia (2016)
In 2006, the Syariah Court has been moved to the new building. The building was built in Jalan Taman Pari, OffJalan Tun Abdul Razak, Ipoh. Building Perak Syariah Court has 5 floors. However, the building height is equal ordinary building 12 floors. This is because Trial Chamber requiring construction space and a predetermined height of building. This building is based on the Yellow Palace Kuala Kangsar. This building also applied in the construction of this building is a style Perak Malay art design can be seen. In fact, it became clear that an identity spirit and culture ofIslam Perak. Level 5 puts the Syanah Court of Appeal, Chief Judge Room, Room Panels Syanah Appeal Court Judge, a Chief Registrar ofthe Syariah Appeal Court and the Office Perak Syariah High Court. Whereas level 4 is for two Trial Chamber ofthe Court Syariah High Court Judge Room , Sulh Room, Bar Room and Room for Men and Women’s Witnesses. Level 3 houses the main operations room, the Administration, Finance and Development, and the Department of Information Technology. There is also a Home Server (Main Server), and Seminar Room Preparation banquet room. Level 2 is the same building with 4 floors, but at this level it’s special for the use and function of Ipoh Syariah lower court. Level 1 is the Ipoh Syariah Lower Court Administration, prayer, men and women equipped with ablution place. Syariah Court building is equipped with 4 lifts namely two lifts for public use, one special elevator to bring in and out ofthe accused or the offender and one special elevator forjudges. Each floor of this building infrastructure facilities provided toilets and dining room. Level G on the ground floor has SBSK Director, Assistant Director SBSK Room, Room SBSK & Records Section, Diner, and Guest Room, Services Division customer’s room, police room and banquet room. While at the level below' is the car park of the judges, officials and staffserving in the Department Perak Syariah Judiciary. Courthouse also has facilities Seminar hall that can accommodate 300 up to 350 participants at any one time. It was built next to the main building Syariah Court building. This hall is equipped with audio-visual system and stage and very suitable for formal occasions or semi-formal